Hematologic secondary malignancies among 102 Chinese patients with Waldenstrom’s macroglobulinemia: a single-center case experience and literature review - Wang, Lingling; Xi, Conglin; Huang, Yongfen; Xu, Hao; Miao, Yuqing; Cheng, Yuexin (Frontiers in Oncology, 2023)
Waldenstrom's Macroglobulinemia (WM) is a rare and indolent B-cell lymphoma.To investigate the type and survival of hematologic secondary malignancies (SMs) in Chinese patients with WM, we retrospectively reviewed the characteristics of 102 patients with WM from February 2002 to May 2023 in our center. Four males and two females were diagnosed with hematologic SMs. Of the 6 patients with hematologic SMs, 1 was diagnosed with Acute Myeloid Leukemia (AML), 1 was Multiple Myeloma (MM), 1 was Myelodysplastic Syndrome (MDS), 1 was B-Acute Lymphoblastic Leukemia (B-ALL), and 2 were Diffuse Large B-cell Lymphoma (DLBCL). The median age was 65.5 years (56-74 years). The median interval time between diagnosis of WM to hematologic SMs was 39.5 months (10-117 months).Five patients died and one survived among the WM with hematologic SMs. Overall survival (OS) was just 33 months (12-119 months) on median. While 32 patients died and 64 survived in the group of WM without hematologic SMs, the median OS was 82 months (3-250 months). It is the first study in the Chinese population on hematologic SMs in WM. The purpose of this study was to investigate the prognosis of hematologic SMs in WM in the Chinese population, as well as to compare the population's characteristics to those of other centers. We investigated the underlying causes further and presented a research strategy for our forthcoming investigation. We intend to investigate risk factors for SMs as well as more accessible screening methods.